Use of carbide slag from acetylene industry for activation of ground granulated blast-furnace slag - Li, Wentao (2022)
This study investigates the use of carbide slag (CS), an industrial by-product generated in acetylene production, as a potential alternative to hydrated lime (HL) for activation of ground granulated blast-furnace slag (GGBS), another industrial by-product generated during the process of iron production. Specimens of CS-GGBS and HL-GGBS pastes with different CS or HL contents were prepared and cured for different periods, and then tested for compressive strength. X-ray diffraction (XRD), thermogravimetric analysis (TGA), Fourier transform infrared spectroscopy (FTIR), and scanning electron microscopy (SEM) were also used to investigate the hydration characteristics of CS-GGBS. The results indicated that CS-GGBS yielded similar compressive strength as HL-GGBS with the same CS/HL content at the same curing periods of 28 and 56 days, i.e. CS could replace HL to activate GGBS, which would result in both environmental and economic benefits. The Ca(OH)2 in CS accelerated the hydration of GGBS, and hence more hydration products were produced. However, excessive CS addition would decrease the GGBS content and increase crystal calcium hydroxide in the matrix, causing strength decrease. Hence, there was an optimum CS/HL content to achieve the highest compressive strength, which was 10% for 7 days and 5% for 28 and 56 days.